Sosialisasi dan Demonstrasi Pengolahan Sampah Rumah Tangga menjadi Produk Eco-enzyme - Yulia Hasni Pratiwi; Sri Winarni Sofya; Lalu Busyairi Muhsin; Muhammad Eka Putra Ramandha; Nyoman Bagus Aji K (Insan Kreasi Media, 2023)
Garbage is a crucial problem faced by all countries in the world, including Indonesia. The waste generation in the province of NTB in 2021 reached 2,637 tons/day, which comes from 10 districts/cities in NTB. Of this amount, only a small portion, namely around 20%, goes to the Final Disposal Site (TPA) and is recycled, while 80% of the total waste is not managed properly. Therefore, to overcome this problem, we offer an innovative solution to process the waste into